The Influence of Project Based Learning Towards Strengthening the Dimensions of Global Diversity and Understanding the Concept of Pancasila Education for Class XI Students of UPT SMAN 3 Bulukumba - Saraswati, Ayuning; Muhajir, Muhajir; Nur, Jumiati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the effect of the Project Based Learning model on strengthening the dimensions of global diversity and increasing the understanding of the concept of Pancasila Education in class XI students of UPT SMAN 3 Bulukumba. This study uses a quantitative approach with a quasi-experimental design involving 62 people from classes XI-1 and XI-5. The results of the study indicate that the application of the Project Based Learning model has a significant effect on strengthening the dimensions of global diversity, especially in terms of tolerance, ability to work together, and appreciation of cultural diversity. In addition, there is a significant increase in the understanding of the concept of Pancasila Education. The average pre-test score in the experimental class was 53 and increased to 89.8 in the post-test, while in the control class it increased from 52.9 to 77. This finding is supported by the results of the t-test which shows a significance value (two-sided) of p = 0.000 <0.05.